IMPACT OF EDUCATIONAL LEVEL IN PUBLIC PERCEPTION ON BIOTECHNOLOGY IN SOUTHERN CEBU, PHILIPPINES - Matildo, Andrea A; Ruiz, Jerome H (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2022)
Since the introduction of biotechnology in the Philippines, the concept and applications have not been well understood due to several barriers that limit information dissemination. The study used a semi- structured interview to assess the likelihood of educational background, which referred to the highest educational attainment, in the public's perception of biotechnology in Southern Cebu. Significant results were found among college graduates being more aware and knowledgeable in biotechnology and its uses in food production. The same group of respondents and those who reached the college level highly trusted information from scientific sources such as academe/researchers, books, seminars, and forums. Those who reached the elementary level and elementary graduates highly trusted and read information from acquaintances, religious figures, and the internet. Individuals who reached college level and college graduates also have a positive attitude and perception towards biotechnology and are willing to attend seminars and participate in policy-making. The same groups of respondents perceived no harm and are less concerned with biotechnology in food production and agricultural development. The result showed that the public perceived biotechnology as a cultural concern in Southern Cebu other than ethical/moral, religious, health, environmental and political. Based on the results, education levels influenced the public's knowledge, perception, and understanding of biotechnology and its applications in food production, public health and safety, and agricultural development. The major practical contribution of this study is that it provides empirical data on the public's attitude, knowledge, and perception of biotechnology that can be used to develop strategies for effective information dissemination.